″Method of Productive Teaching of Computer Disciplines in the System of Fundamental Vocational Training of Future IT Professionals″ - Bardus, I. O. (Problems of Engineer-Pedagogical Education, 2018)
The quality improvement of training future specialists in the field of information technology requires the development of productive teaching methods based on the fundamentalization of education. The article theoretically substantiates and outlines the devised method of training future IT specialists which was designed to help them perform productively professional functions in the realm of the development of new computer hardware and software or improvement of the existing one. The suggested method of productive activity is a combined method as it involves the use of the method of heuristics, retrospective analysis of IT objects, the matrix of the development of features and the fundamental bases of an IT object. The main stages of the method of productive training are motivation-objective, preparatory-substantial, operational-activity, control-correction and evaluative-productive. The outlined method of productive training corresponds to the structure of the professional activity of the IT specialist, and helps improve basic IT objects or create new ones on the basis of fundamental philosophical, natural and mathematical laws and categories. The obtained results will be used to develop a fundamentalized methodological system for training computer disciplines to future specialists in the field of information technology.